A first-hand experience for a second-hand product : the success of online luxury resellers - Duarte, Beatriz Maria Estrela (2020)
The purpose of this research is to understand how luxury resellers successful create value-added propositions within the online context, posing a challenge to the exclusivity inherent to the luxury reality. We used a qualitative approach to analyse three online second-hand players and drew our conclusions on the Business Model Canvas. The findings of the present research show that the success of luxury online resellers is built on (1) a diversified, personalised and curated luxury assortment, (2) wider customer reach enabled by online, (3) trusted authentication processes, (4) powerful network effect, (5) proprietary technology and in-house skilled staff. These are assets difficult to replicate which raises barriers to entry and are further complemented with offline expansion and partnerships with luxury brands. This research is relevant for both incumbent companies and new entrants alike, as well as luxury companies to better understand the value of the second-hand luxury market.